DEVELOPING MATERIALS TO PROVIDE LANGUAGE LEARNING ENVIRONMENT TO SUPPORT GRADE 5 STUDENTS’ LITERACY SKILLS IN ENGLISH - Himadara, Ida Ayu; Marhaeni, A.A.I.N; Putu Artini, Luh (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
ABSTRACT This study aimed at describing the English literacy coverage of grade 5 students of Primary Schools in Bali, developing materials to support grade 5 students? English literacy skills, and investigating the quality and the effectiveness of the developed materials in supporting grade 5 students? English literacy skills. The subjects of this study were the grade 5 students of  Public Primary Schools in Bali. The data were gathered through documentation, expert judgment, observation, syllabus analysis, conducting test and questionnaires. Based on the competency standard and the basic competence in the syllabus, the English Literacy coverage were about understanding and copying some simple texts and sentences. The materials that need to be developed were based on the topics in the syllabus used by the schools. The developed materials were classified into 4 topics: Animals, Food and Drink, Classroom Objects, and Public Places. The materials designed were emphasized on the practices of English literacy skills which consisted of Topical Vocabulary, Grammar Focus, Everyday Expression, Language Games and Time for Story.  The quality measurement showed Sr<4.485=3.6<4.485, means that the materials were categorized as good materials. The effectiveness of measurement showed that the materials of Rich Language Learning Environment are effective to support the grade 5 students? English Literacy Skills.   Keywords: TEYL, Literacy Skills, Rich Language Learning Environment